Kategorie zdrowia, choroby w kontekście niepełnosprawności – ujęcie teoretyczne - Antoszewska, Beata; Bartnikowska, Urszula (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Life is of great value to any human being and can be considered to be a fundamental concept. It has a determined temporal dimension, although it remains unknown to a given individual. An overview of relevant literature demonstrates that much has been written on the subject of health and ability and it has been quite extensively discussed. Yet this concept remains valid because its meaning is constantly changing. People are not able to completely free themselves from diseases/disabilities. During one’s lifetime one is exposed to periodic or permanent difficulties or limitations. Human life involves functioning on the border of health and disease, full ability and disability. It is important, however, how one deals with difficulties that one must face, who one will meet on one’s way and what kind of help will be offered. This paper aims to present a theoretical framework of health and disease, including chronic disease and disability.